2012
DOI: 10.1111/j.1399-0012.2012.01654.x
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen mismatches associated with increased risk of rejection, graft failure, and death independent of initial immunosuppression in renal transplant recipients

Abstract: Human leukocyte antigen (HLA) mismatches have been shown to adversely affect renal allograft outcomes and remain an important component of the allocation of deceased donor (DD) kidneys. The ongoing importance of HLA mismatches on transplant outcomes in the era of more potent immunosuppression remains debatable. Using Australia and New Zealand Dialysis and Transplant Registry, live and DD renal transplant recipients between 1998 and 2009 were examined. The association between the number of HLA mismatches and HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 15 publications
2
66
0
5
Order By: Relevance
“…The major impact of matching is due to the HLA-DR and -B loci, with the HLA-A locus much less significant (3,28). The HLA-DR locus seems to have the biggest overall impact (3,29). In our study, we found the biggest AR impact at the HLA-B and -DR loci-a finding that parallels their relative importance in kidney transplants (3).…”
Section: Discussionsupporting
confidence: 71%
“…The major impact of matching is due to the HLA-DR and -B loci, with the HLA-A locus much less significant (3,28). The HLA-DR locus seems to have the biggest overall impact (3,29). In our study, we found the biggest AR impact at the HLA-B and -DR loci-a finding that parallels their relative importance in kidney transplants (3).…”
Section: Discussionsupporting
confidence: 71%
“…An association between HLA-ABDR mismatches and acute rejection risk in live and deceased donor kidney transplantation has been shown in multiple studies, with this association persisting even in the era of modern immunosuppression (3). In a retrospective study of 82 pediatric kidney transplant recipients with prior failed grafts, #30% of recipients developed de novo anti-HLA antibody predominantly against HLA-DQ (13).…”
Section: Discussionmentioning
confidence: 99%
“…Matching at the HLA-ABDR loci remains the cornerstone of deceased donor kidney allocation in Australia and worldwide because of the association between incremental HLA-ABDR mismatches and increased risk of rejection and/or graft loss after kidney transplantation (1)(2)(3). Although differences in HLA-DQ matching between donors and recipients have been shown to be associated with adverse graft outcomes, matching at the HLA-DQ locus is not explicitly considered in the allocation algorithm for deceased donor kidney transplantation (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Even in the era of modern immunosuppression, HLA matching remains one of the major criterion in deceased donor kidney allocation in Australia and worldwide. 3-5 Serological typing at the HLA-ABDR loci is used universally to determine the number broad antigen HLA mismatches and is the standard triage test for the assessment of immunological compatibility between potential donors and recipients.…”
mentioning
confidence: 99%